Que peut-on faire des théories ? Essai de classification des modélisations en architecture - Louis Vitalis; François Guéna (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
In architecture, « theory » seems not to have the same meaning depending on the theory, moreover, the use one can make out of it is not predetermine by the used theory. The notion of modeling, in use in contemporary sciences to describe new research practices, will allow us to understand the transfer between the theory and its use. After considering the way of tracking theories in architecture and after considering the funding epistemological principles of the relation theory-practice, we will propose a classification of architectural modeling following three practices: design, analysis, and simulation.